View of Vienna across from the Landstrasse - Piringer, Ferdinand, 1780-1829 (engraver):::Creator::::::::::::; Janscha, Laurenz, 1749-1812 (artist) ; Laborde, Alexandre Louis Joseph de, 1774-1842 (author):::Contributor::::::::::::
Aquatint image of the Landstrasse in Vienna